2013
DOI: 10.1007/s00520-013-1876-6
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of quality of life in advanced cancer patients with bone metastases undergoing palliative radiation treatment

Abstract: Baseline KPS had the greatest influence on EORTC QLQ-C30 domain scores. Age, education level, and employment status had significant impacts, although on fewer domains. Further studies that investigate baseline determinants are worthwhile to clarify relationships in order to care for patients more effectively at the end of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 27 publications
2
28
1
1
Order By: Relevance
“…To determine whether patients with an intermediate level of PD at baseline might have more chance of converting to a high level of PD during follow-up, the patients below the cutoff value were divided into two groups: low (7)(8)(9)(10)(11) and an intermediate (12)(13)(14)(15)(16) level.…”
Section: Psychological Distressmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine whether patients with an intermediate level of PD at baseline might have more chance of converting to a high level of PD during follow-up, the patients below the cutoff value were divided into two groups: low (7)(8)(9)(10)(11) and an intermediate (12)(13)(14)(15)(16) level.…”
Section: Psychological Distressmentioning
confidence: 99%
“…Painful bone metastases have a negative impact on the QoL of patients [5,6]. Studies show that radiotherapy stabilizes or improves QoL [7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike populations without cancer, insomnia is inversely related with age in patients with cancer at mixed sites [21,23,28,44] and also among men with prostate cancer [42,49] . Younger men are also more likely to develop insomnia syndrome [42] , suggesting that younger men may have more trouble adjusting to their 'new normality' and consequently, are more susceptible to chronic sleeping difficulties.…”
Section: Predisposing Factors Agementioning
confidence: 99%
“…One such study described that the onset of symptoms was secondary to prostate cancer diagnosis in doi: 10.18282/amor.v2.i2.94 54% of men experiencing insomnia syndrome [42] . The majority of longitudinal studies described the highest prevalence of insomnia, or highest insomnia scores indicating worse symptomology, at the time point closest to diagnosis [23][24][25]49] . In one longitudinal study, 15% of the men reported that their first episode of insomnia coincided with their diagnosis [24,25] .…”
Section: Precipitating Factors Cancer Diagnosismentioning
confidence: 99%
See 1 more Smart Citation